Overview of the use of biochar from main cereals to stimulate plant growth - Martínez-Gómez, Ángela; Poveda, Jorge; Escobar, Carolina (Frontiers in Plant Science, 2022)
The total global food demand is expected to increase up to 50% between 2010 and 2050, hence there is a clear need to increase plant productivity with little or no damage to the environment. In this respect, biochar is a carbon-rich material derived from the pyrolysis of organic matter at high temperatures with a limited oxygen-supply, with different physicochemical characteristics which depend on the feedstock and pyrolysis conditions. When used as a soil amendment, it has shown many positive environmental effects such as carbon sequestration, reduction of greenhouse gases emissions and soil improvement. Biochar application has also shown huge benefits when applied to agri-systems, among them, the improvement of plant growth either in optimal conditions or under abiotic or biotic stress. Several mechanisms, such as enhancing the soil microbial diversity and thus increasing soil nutrient-cycling functions, improving soil physicochemical properties, stimulating the microbial colonization, or increasing soil P, K, or N content, have been described to exert these positive effects on plant growth, either alone or in combination with other resources. In addition, it can also improve the plant antioxidant defenses, an evident advantage for plant growth under stress conditions. Although agricultural residues are generated from a wide variety of crops, cereals account for more than half of the world’s harvested area. Yet, in this review, we will focus on biochar obtained from residues of the most common and relevant cereal crops in terms of global production (rice, wheat, maize, and barley) and in their use as recycled residues to stimulate plant growth. The harvesting and processing of these crops generate a vast number and variety of residues that could be locally recycled into valuable products such as biochar, reducing the waste management problem and accomplishing the circular economy premise. However, very scarce literature focused on the use of biochar from a crop to improve its own growth is available. Herein, we present an overview of the literature focused on this topic, compiling most of the studies and discussing the urgent need to deepen into the molecular mechanisms and pathways involved in the beneficial effects of biochar on plant productivity.